Reimagining Animism: The Ecocritical Psyche In Malay Folklore - Ahmad Kushairi, Azalea; Zainal, Zainor Izat (SARE: Southeast Asian Review of English, 2025)
This paper explores the complex interplay between human consciousness, nature, and spiritual realms in folklore from the Malay world through the lens of the ecocritical psyche. By reimagining animism beyond colonialist interpretations, the study reveals a worldview where the psyche extends into the environment, and life, death, morality, and community are interconnected across vertical and horizontal axes. The vertical axis governs transitions between realms, with ancestors, death, and spiritual beliefs exemplifying the reciprocal relationship between the living and the spiritual world. In contrast, the horizontal axis highlights the community’s responsibility to maintain harmony, reflected through rituals like the Turun Ka Bondang ceremony and Ritual of Sebayuh. Through analyses of tales such as the crocodile “Buwaya” and “Kangkuksa Pelesit,” the paper also demonstrates how forces of good and evil are intertwined with cultural, ecological, and psychological dimensions. Fundamentally, Malay animism, as reflected in these stories, offers a sophisticated system of ecological and psychological integration, where balance is not fixed but actively cultivated. This study affirms that sustainable relationships with the natural world, spiritual realms, and communal life are essential for psychological wholeness and ecological harmony in the Malay cosmos.